2013
DOI: 10.30539/iraqijvm.v37i1.318
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Local Laying Hen’s Egg Shell with Salmonella Serotypes

Abstract: Fifty locally laying hen’s eggs random samples were collected from different markets of Baghdad city in order to investigate the presence of Salmonellae Spp. in shell of those eggs. The samples were collected during the period from March 2012 to May 2012.The samples were directly transferred to the Food hygiene laboratory and analyzed immediately without further storage.The isolation and identification methods include: (pre-enrichment) culture stage by peptone water then, (Selective enrichment) culture stage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…Additionally, this study with agreement of ( Harb et al , 2019 ) who reported that 26% of fresh retail chicken meat samples and 39% of raw chicken carcasses were contaminated with Salmonella spp . In Iraq, the results of this study were lower than the results of ( Jaffer, 2013 ) who isolated S. enterica in Iraq from chicken eggs and recorded 30%. Also were lower than the results of ( Siddique et al , 2021 ) who isolated S. enterica from poultry and its associated food products in Pakistan, that recorded 25.67%.…”
Section: Discussioncontrasting
confidence: 92%
“…Additionally, this study with agreement of ( Harb et al , 2019 ) who reported that 26% of fresh retail chicken meat samples and 39% of raw chicken carcasses were contaminated with Salmonella spp . In Iraq, the results of this study were lower than the results of ( Jaffer, 2013 ) who isolated S. enterica in Iraq from chicken eggs and recorded 30%. Also were lower than the results of ( Siddique et al , 2021 ) who isolated S. enterica from poultry and its associated food products in Pakistan, that recorded 25.67%.…”
Section: Discussioncontrasting
confidence: 92%
“…All fecal samples were counted for Salmonella using the previously reported threetube most probable number (MPN) technique according to (11). Salmonella suspected samples were streaked over xylose lysine deoxycholate (XLD) and Salmonella Brilliance agar plates (Oxoid, Australia) to determine whether they contained Salmonella spp (12).…”
Section: Counting the Number Of Salmonella In Fecal Samplesmentioning
confidence: 99%
“…The Wizard genomic DNA purification kit (Promega, Australia), was used to extract the DNA from all the tissue samples in accordance manufacture guideline (12).…”
Section: Extraction Of Bacterial Dna From Internal Organsmentioning
confidence: 99%
“…The department of pathology and poultry diseasescollege of veterinary medicine-University of Baghdad had an unpublished isolate of the H5N1 influenza virus (allantoic fluid). The ELD50 was determined to be 10 9.5 by a hemagglutination test in embryonated chicken eggs, which was then utilized to challenge in 100ELD50 10 7.5 using Reed and Muench's approach (15). The sample was kept until usage in a deep freezer at -80ºC.…”
Section: Prepared the Viral Inoculummentioning
confidence: 99%